Meniscus implant and preparation method thereof
By using artificial meniscus implants constructed with degradable hydrogels and composite fibers, combined with the release of growth factor in platelet-rich plasma, the shortcomings in structural mechanics and biological activity of existing implants are solved, and the effect of repairing meniscus damage in situ in vivo is achieved.
Patent Information
- Application Number
- CN202411762585.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
Existing meniscus implants are difficult to meet biomechanical requirements in structural mechanics, and the material's biological activity and autocompatibility are insufficient, resulting in a short implant life and poor repair effect.
Degradable hydrogels are used as the matrix, composite fibers are used as the skeleton, and platelet-rich plasma is used as the source of growth factor release. Through the composite construction of silk fibers and degradable fibers, artificial meniscus implants with biological activity and bionic structure are formed.
It realizes the construction of autologous collagen fiber structure in situ in vivo, effectively repair meniscus damage, enhances the biocompatibility and mechanical properties of the implant, extends the implant lifespan, and avoids the abnormal cell differentiation and apoptosis and death problems in traditional methods.
Smart Images

Figure CN119564934A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to a meniscus implant and a preparation method thereof. Background Art
[0002] The meniscus of the knee joint is a fibrous cartilage located on the medial and lateral articular surfaces of the tibial plateau. Its biomechanical anisotropy and heterogeneity can meet various mechanical requirements of the knee joint, such as load-bearing, maintaining knee coordination, stabilizing movement and absorbing shock. The meniscus of the knee joint of adults can be damaged due to various external factors such as age, occupation and work intensity. Meniscus injuries in young and middle-aged patients are often lacerations, while meniscus injuries in elderly patients are often closely related to degenerative changes. If meniscus injuries are not treated reasonably in time, they often cause osteoarthritis, and the main reasons for patients to seek medical treatment are increased pain and functional impairment. The meniscus can be divided into the following three areas, namely the white area, the red area and the red and white junction area. The white area has no blood vessels and no local blood supply. Once damaged, it is difficult to complete tissue repair. Therefore, it is difficult to repair the meniscus after injury, and most patients have a poor prognosis. Therefore, repairing and reconstructing the meniscus injury, restoring its joint function and preventing joint degeneration have always been one of the problems to be solved in the field of orthopedic medicine.
[0003] At present, the clinical treatment strategy mainly repairs the meniscus or replaces and reconstructs it through tissue engineering methods such as local repair, allogeneic meniscus transplantation, and artificial meniscus replacement to restore joint mobility. However, local repair only targets mild tear injuries, and allogeneic meniscus transplantation is limited by issues such as donor sources and immune rejection. Artificial cartilage prostheses are often prepared in a standardized manner using a single material. Not only is it difficult for the structural mechanics to meet the requirements of joint biomechanics, but the morphological characteristics cannot fully match the joint anatomical structure. Sequelae such as loosening and wear result in an implant life of less than 15 years.
[0004] In recent years, the use of autologous chondrocyte transplantation (ACI) combined with artificial degradable implants to construct autologous chondrocyte transplantation (MACI) for cartilage repair and replacement has become a new tissue regeneration method. Among them, MACI can greatly simplify the surgical steps on the basis of ACI and improve the safety and effectiveness of artificial cartilage (201810559175.4, 201710952296.0). However, artificial cartilage implant materials often use degradable polymer materials such as polylactic acid (PLA) and polycaprolactone (PCL), which have poor bone inductivity and weak structural properties. The initial strength is difficult to meet the support of the meniscus structure. Although the material can be modified by doping with zero-dimensional functional particles such as hydroxyapatite, calcium phosphate, and graphene to improve its biological activity, it is still a homogeneous structure, which is completely different from the collagen fiber meniscus structure and does not have anisotropic structural properties.
[0005] On the other hand, although existing patents (CN201710999938.2, US2021 / 0137691) have proposed constructing a bionic artificial meniscus implant with a meniscus collagen fiber structure through a weaving process, which meets the biomechanics of an artificial meniscus in terms of structural mechanics, the use of high-performance fibers such as carbon fiber and Kevlar can cause allergic and rejection reactions in patients, and has no biological activity, making it difficult to promote meniscus repair and reconstruction.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a meniscus implant that can construct an autologous collagen fiber structure in situ in vivo for in vivo repair of meniscus damage.
[0008] The second object of the present invention is to provide a method for preparing the above meniscus implant, which can be used for batch preparation or personalized customization of meniscus.
[0009] In order to achieve the above objectives, the following technical solutions are adopted:
[0010] In a first aspect, the present invention provides a meniscus implant comprising a degradable hydrogel, a composite fiber, and platelet-rich plasma (PRP);
[0011] The meniscus implant uses a degradable hydrogel as a matrix and composite fibers as a skeleton; the composite fibers and platelet-rich plasma are distributed inside the degradable hydrogel;
[0012] The composite fiber is mainly obtained by composite twisting of degradable fiber and silk fiber; the degradable fiber releases calcium ions after degradation.
[0013] As a further technical solution, the degradable hydrogel is mainly obtained by cross-linking a precursor solution;
[0014] Preferably, the precursor comprises at least one of silk fibroin, agarose, alginate, collagen, gelatin, hyaluronic acid, chitosan, gellan gum, cellulose, fibrin, polyvinyl alcohol, polyethylene glycol, polyacrylamide or poly(hydroxyethyl methacrylate);
[0015] Preferably, in the precursor solution, the mass ratio of the precursor to water is 1:5 to 1:10;
[0016] Preferably, the mass ratio of the platelet-rich plasma to the precursor solution is 1:5 to 1:15.
[0017] As a further technical solution, the mass proportion of the composite fiber is 15% to 55%;
[0018] Preferably, the twist of the composite fiber is 10 to 60 twists / m;
[0019] Preferably, in the composite fiber, the volume ratio of the degradable fiber to the silk fiber is 1:0.5 to 1:5;
[0020] Preferably, in the meniscus implant, the composite fibers are braided into a braid.
[0021] As a further technical solution, the degradable fiber is a degradable inorganic fiber;
[0022] Preferably, the degradable inorganic fiber comprises calcium phosphate-based glass fiber;
[0023] Preferably, the mass percentage of calcium in the degradable inorganic fiber is 0.05% to 3%.
[0024] As a further technical solution, the degradable fiber is a degradable organic fiber;
[0025] Preferably, the degradable organic fiber comprises polyvinyl alcohol fiber, polyvinyl pyrrolidone, polylactic acid or polycaprolactone;
[0026] Preferably, the degradable organic fiber is doped with a soluble calcium salt;
[0027] Preferably, the soluble calcium salt includes calcium chloride, and the mass proportion of the soluble calcium salt in the degradable organic fiber is 0.1% to 5%.
[0028] In a second aspect, the present invention provides a method for preparing the above meniscus implant, comprising the following steps:
[0029] a. preparing a precursor solution of the degradable hydrogel, and then mixing it with platelet-rich plasma to obtain a precursor mixed solution;
[0030] b. Weaving the composite fibers to obtain a braided fabric, then stacking the braided fabric in a mold, adding the precursor mixed solution obtained in step a, and preparing a meniscus implant after cross-linking.
[0031] As a further technical solution, the composite fibers in the braided fabric are bonded with a binder.
[0032] As a further technical solution, the precursor is at least one of polyvinyl alcohol, hyaluronic acid, chitosan, gelatin, cellulose or agarose;
[0033] The cross-linking method comprises: freezing and cross-linking the precursor mixed solution in an environment of -30 to -10°C for 6 to 12 hours, then thawing in an environment of 0 to 8°C for 6 to 12 hours, and preparing a meniscus implant after 3 to 6 cycles.
[0034] As a further technical solution, the precursor is at least one of polyacrylamide, polyhydroxyethyl methacrylate, silk fibroin, alginate, collagen, gellan gum, fibrin or polyethylene glycol;
[0035] The precursor mixed solution also contains a photoinitiator and a monomer;
[0036] The cross-linking method comprises: cross-linking a precursor mixed solution under ultraviolet light for 0.5 to 3 hours to prepare a meniscus implant.
[0037] As a further technical solution, the photoinitiator and the monomer are mixed in a mass ratio of 0.01:100 to 1:100;
[0038] Preferably, the photoinitiator comprises at least one of phenyl-2,4,6-trimethylbenzoyl lithium phosphite, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide;
[0039] Preferably, the monomer includes at least one of a polyacrylamide monomer, a polyhydroxyethyl methacrylate monomer or a polyurethane acrylate monomer.
[0040] Compared with the prior art, the meniscus implant provided by the present invention has the following technical effects:
[0041] 1. With natural silk as the reinforcing body and degradable hydrogel as the matrix, a composite artificial meniscus implant with biological activity and full compatibility with the human body is constructed; it effectively avoids the problem that the structural performance of traditional single-material implants is isotropic and cannot meet the requirements of bionic mechanics.
[0042] 2. The degradable fibers in the matrix are used as the growth factor release switch, and the PRP in the hydrogel matrix is used as the source of growth factor release. After implantation in the body, the fiber degradation can controllably release calcium ions, stimulate PRP to release various growth factors, and induce the synovial mesenchymal stem cells in the joint capsule to grow into the fiber channels in the meniscus implant, and differentiate into cartilage structures by attaching to natural silk, forming a collagen fiber reinforced structure similar to the human meniscus. The present invention not only realizes the in-situ construction of an artificial meniscus with a bionic structure, but also avoids the problems of abnormal cell differentiation, withering and death in the in vitro composite culture of autologous cells in the traditional chondrocyte migration (MCAI) method.
[0043] 3. The preparation method of the meniscus implant provided by the present invention can be used to customize the design of the meniscus injury site and make a customized artificial meniscus implant that is completely compatible with the injured site, so as to ensure stable fit with the joint movement behavior and avoid loosening and slipping. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 This is a schematic diagram of the principle of in-situ shaping of collagen fibers after the meniscus implant of the present invention is implanted into a joint. DETAILED DESCRIPTION
[0046] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0047] In a first aspect, the present invention provides a meniscus implant, comprising a degradable hydrogel, composite fibers and platelet-rich plasma;
[0048] The meniscus implant uses a degradable hydrogel as a matrix and composite fibers as a skeleton; the composite fibers and platelet-rich plasma are distributed inside the degradable hydrogel;
[0049] The composite fiber is mainly obtained by composite twisting of degradable fiber and silk fiber; the degradable fiber releases calcium ions after degradation.
[0050] Existing artificial meniscus implants mainly construct porous structures to facilitate the attachment and growth of meniscus chondrocytes, and rely on porous branches to form cartilage structure tissue; however, for the damaged area without blood supply, due to the extremely small number of active cells, it is almost impossible to generate cartilage tissue after implanting the scaffold. Although cell growth and differentiation can be stimulated by loading bioactive growth factors, surface treatment methods are often used, and it is impossible to maintain stable growth factor sustained release control for a long time; and meniscus implants are often made of homogeneous polymer materials, which do not have anisotropic structures similar to natural menisci, and their biomechanical properties are quite different from those of actual human cartilage. The meniscus implant provided by the present invention constructs a bionic structure similar to the natural meniscus by weaving composite fibers. After being implanted in the damaged area of the joint meniscus, the meniscus is repaired through the following physiological behaviors (such as Figure 1 shown):
[0051] a. The degradable fiber degrades and slowly releases calcium ions into the hydrogel matrix, stimulating the PRP in the hydrogel to release a variety of growth factors and proteins, including: platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β), epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), osteocalcin, osteonectin, fibrinogen, vitronectin, fibronectin, thrombin response protein-1 and other growth factors, which enter the joint meniscus.
[0052] b. Growth factors are slowly released into the joint environment, inducing synovial mesenchymal stem cells to migrate to the meniscus implant and attach to the implant surface, initially improving problems such as insufficient blood supply to the white area of the meniscus and few active cells.
[0053] c. With the decomposition of the degradable fibers and the release of calcium ions, fiber channels of natural silk fibers are gradually formed in the hydrogel matrix after degradation.
[0054] d. Under the regulation of growth factors, synovial mesenchymal stem cells are stimulated to migrate into the pores in the hydrogel matrix.
[0055] e. At the same time, synovial mesenchymal stem cells differentiate into meniscus fibrocartilage cells after being induced by growth factors, and the silk fibers in the pores grow into and form cartilage tissue, thereby constructing a collagen fiber cartilage structure similar to the natural meniscus. In addition, PRP can inhibit the release of inflammatory cytokines, promote tissue healing and regeneration, capillary formation, and produce fibrin matrix to provide support for tissue growth.
[0056] In some optional embodiments, the degradable hydrogel is mainly obtained by cross-linking a precursor solution;
[0057] Preferably, the precursor includes but is not limited to at least one of silk fibroin, agarose, alginate, collagen, gelatin, hyaluronic acid, chitosan, gellan gum, cellulose, fibrin, polyvinyl alcohol, polyethylene glycol, polyacrylamide or poly(hydroxyethyl methacrylate), or other precursors with degradable function known to those skilled in the art;
[0058] Preferably, in the precursor solution, the mass ratio of the precursor to water may be, for example, but not limited to, 1:5, 1:7, 1:9 or 1:10;
[0059] Preferably, the mass ratio of the platelet-rich plasma to the precursor solution may be, for example, but not limited to, 1:5, 1:7, 1:9, 1:11, 1:13 or 1:15.
[0060] In some optional embodiments, the mass percentage of the composite fiber may be, for example, but not limited to, 15%, 25%, 35%, 45% or 55%;
[0061] Preferably, the twist of the composite fiber may be, for example, but not limited to, 10 twists / m, 20 twists / m, 30 twists / m, 40 twists / m, 50 twists / m or 60 twists / m;
[0062] Preferably, in the composite fiber, the volume ratio of the degradable fiber to the silk fiber may be, for example, but not limited to, 1:0.5, 1:1, 1:3 or 1:5;
[0063] Preferably, in the meniscus implant, the composite fibers are braided into a braid.
[0064] In some optional embodiments, the degradable fiber is a degradable inorganic fiber;
[0065] Preferably, the degradable inorganic fiber comprises calcium phosphate-based glass fiber;
[0066] Preferably, the mass percentage of calcium in the degradable inorganic fiber may be, for example, but not limited to, 0.05%, 0.1%, 0.5%, 1%, 2% or 3%. The calcium may be released into the degradation medium in the form of ions as the fiber degrades.
[0067] It should be noted that calcium-phosphorus-based glass fibers can undergo hydrolysis reactions with water molecules and break and decompose, releasing phosphorus and calcium elements in the form of ions that are slowly released into the degradation medium. The calcium ion degradation and release rate in the body environment is 0.5 to 2.5×10 -9 kg m -2 s -1 The calcium ions released from the degradable fibers can not only act on the growth of bone cells, but also activate the release of growth factors in platelet-rich plasma, promoting cell differentiation to form cartilage structure.
[0068] In some optional embodiments, the degradable fiber is a degradable organic fiber;
[0069] Preferably, the degradable organic fiber includes but is not limited to polyvinyl alcohol fiber, polyvinyl pyrrolidone, polylactic acid or polycaprolactone;
[0070] Preferably, the degradable organic fiber is doped with soluble calcium salt, and its calcium ion degradation and release rate in the body environment is 0.3 to 1×10 -9 kg m -2 s -1 , achieving the sustained release of calcium ions in the body as the fibers degrade;
[0071] Preferably, the soluble calcium salt includes but is not limited to calcium chloride, and the mass proportion of the soluble calcium salt in the degradable organic fiber may be, for example, but not limited to, 0.1%, 0.5%, 1%, 3% or 5%.
[0072] In a second aspect, the present invention provides a method for preparing the above meniscus implant, comprising the following steps:
[0073] a. preparing a precursor solution of the degradable hydrogel, and then mixing it with platelet-rich plasma to obtain a precursor mixed solution;
[0074] b. Weaving the composite fibers to obtain a braided fabric, then stacking the braided fabric in a mold, adding the precursor mixed solution obtained in step a, and preparing a meniscus implant after cross-linking.
[0075] In some optional embodiments, the method for preparing platelet-rich plasma comprises the following steps:
[0076] Disinfect the patient's own veins, draw 20-100 mL of venous blood, add 10% sodium citrate anticoagulant and use gradient centrifugation (differential centrifugation), centrifuge for 10 minutes, draw the upper plasma layer and the solution above 2 mm below the dividing line into a new centrifuge tube, centrifuge for another 10 minutes, take out 2 mL of PRP from the lower layer, discard the remaining upper liquid, shake and oscillate for 30 seconds to prepare concentrated PRP.
[0077] In some optional embodiments, in the composite fiber, the degradable fiber and the silk fiber bundle maintain the same number of strands and twist, are twisted and compounded in a Z-twist form, have a twist of 10 to 60 twists / m, and maintain the same twist as the degradable fiber bundle or the natural silk fiber bundle.
[0078] In some optional embodiments, the fiber form is a continuous form, including: weaving, unidirectional 0°, 0° / 90° staggered, 0° / 45° staggered, 0° / 45° / 90° and other forms, either alone or in combination; wherein the weaving form includes one or more of plain weave, twill, and satin weave.
[0079] In some optional embodiments, the composite fibers in the woven fabric are bonded with a binder.
[0080] In some optional embodiments, the woven fabric is a fiber mat, and the preparation method thereof is as follows:
[0081] 1. Solution spraying method: For room temperature liquid adhesive (such as polyethylene glycol, etc.) or adhesive soluble in water or organic solvent at room temperature (such as polyvinyl alcohol, etc.), mix the adhesive with deionized water or organic solvent in a certain proportion, and stir at a constant speed for 1 to 5 hours to evenly disperse the adhesive to form a solution. Spray the mixed solution onto the surface of the woven fiber through a surface spraying process, and place it in a 60-80°C oven to dry for 1 to 2 hours to form a stable fiber felt.
[0082] 2. Fiber fabric impregnation method: Mix a room temperature adhesive (such as polyethylene glycol, etc.) soluble in water or organic solvent with deionized water or organic solvent to fully disperse it, and stir it at a constant speed for 1 to 5 hours to form a homogeneous mixed solution. Then immerse the continuous fiber fabric in the solution for 0.1 to 0.5 hours, then take it out and place it in a 60 to 80 ° C oven to dry for 1 to 3 hours to form a stable fiber felt.
[0083] In some optional embodiments, the precursor is at least one of polyvinyl alcohol, hyaluronic acid, chitosan, gelatin, cellulose or agarose;
[0084] The cross-linking method comprises: freezing and cross-linking the precursor mixed solution in an environment of -30 to -10°C for 6 to 12 hours, then thawing in an environment of 0 to 8°C for 6 to 12 hours, and preparing a meniscus implant after 3 to 6 cycles.
[0085] In some optional embodiments, the precursor is at least one of polyacrylamide, polyhydroxyethyl methacrylate, silk fibroin, alginate, collagen, gellan gum, fibrin or polyethylene glycol;
[0086] The precursor mixed solution also contains a photoinitiator and a monomer;
[0087] The cross-linking method comprises: cross-linking a precursor mixed solution under ultraviolet light for 0.5 to 3 hours to prepare a meniscus implant.
[0088] In some optional embodiments, the photoinitiator and the monomer are mixed in a mass ratio of 0.01:100 to 1:100;
[0089] Preferably, the photoinitiator includes but is not limited to at least one of phenyl-2,4,6-trimethylbenzoyl lithium phosphite, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide;
[0090] Preferably, the monomer includes but is not limited to at least one of polyacrylamide monomer, polyhydroxyethyl methacrylate monomer or polyurethane acrylate monomer.
[0091] The preparation method of the meniscus implant provided by the present invention can be used for batch preparation or personalized customization of meniscus. The preparation method of the personalized customized mold is as follows:
[0092] 1. Data scanning: Performing nuclear magnetic resonance imaging on the patient's knee joint to obtain a nuclear magnetic resonance two-dimensional image of the knee joint;
[0093] 2. Data processing: Import the healthy knee joint data of the patient stored in step 1 into the biological 3D software, segment and mesh the meniscus, obtain the 3D models of the medial and lateral menisci, mirror the 3D models, obtain the 3D model of the meniscus suitable for the affected side injury, and then perform local correction processing;
[0094] 3. 3D model construction and mold design: import the 3D model of the meniscus after triangular facet optimization into UG design software for mold remodeling to make a 3D mold model;
[0095] 4. Mold preparation: Using transparent PMMA, based on the manufactured three-dimensional mold model, a light-transmitting three-dimensional mold is prepared by CNC machining, light-curing 3D printing, etc.
[0096] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0097] Example 1
[0098] (1) Preparation of composite fibers for meniscus implants:
[0099] Materials: The reinforced structure is made of degradable calcium phosphate glass fiber, in which the mass ratio of calcium is 1%.
[0100] Yarn form: Calcium phosphate glass fiber and silk fiber are twisted in S-twist form with a twist of 50 twists / m to form a single yarn, and then the two are twisted and compounded in Z-twist form to form a plied yarn with a twist of 50 twists / m.
[0101] Fiber mat morphology: The yarn is woven in plain weave to form a fiber fabric structure, and then polyvinyl alcohol is mixed with deionized water to fully disperse it, and a homogeneous mixed solution is formed by stirring at a constant speed for 1 hour. The fiber fabric is immersed in the solution for 0.5 hours, and then taken out and placed in a 60°C oven for 1 hour to form a stable fiber mat.
[0102] (2) Preparation of meniscus implant matrix:
[0103] Materials: Polyvinyl alcohol is used as the meniscus matrix.
[0104] Preparation of platelet-rich plasma: 50 mL of venous blood was drawn from the patient, 10% sodium citrate anticoagulant was added, and the blood was centrifuged for 10 min using gradient centrifugation (differential centrifugation). The upper plasma layer and the solution above 2 mm below the dividing line were aspirated into a new centrifuge tube, and the blood was centrifuged again for 10 min. 2 mL of PRP was taken from the lower layer, and the blood was shaken for 30 s to obtain concentrated PRP.
[0105] Molding process: Using the freeze-thaw process, the polyvinyl alcohol pellets were evenly mixed with deionized water in a mass ratio of 1:5, and magnetically stirred at 300RPM / min in a 60°C water bath for 1 hour to form a homogeneous solution. The treated PRP and hydrogel precursor solution were evenly mixed in a ratio of 1:10, and dispersed by magnetic stirring at 300RPM / min at room temperature. Then, the bubbles were removed by vacuum in a vacuum box at 50°C to form a homogeneous, bubble-free, low-viscosity hydrogel precursor solution.
[0106] (3) Preparation of meniscus implants:
[0107] Component content: The fiber-reinforced structure accounts for 50% by weight in the meniscus implant.
[0108] Molding process: Standard mold molding is adopted, based on resin transfer molding (RTM) technology, the cut fiber felts are stacked in the RTM mold, the catheter is connected, and the hydrogel precursor is injected into the mold at a uniform speed to make the precursor completely infiltrate the composite fiber felt. According to the freeze-thaw method, it is frozen and cross-linked at -20°C for 12 hours, and then thawed at 4°C for 12 hours. This cycle is repeated 3 times, and then the artificial meniscus implant is removed.
[0109] (4) Performance characterization of meniscus implants:
[0110] The calcium ion release rate was 1×10 -9 kg m -2 s -1 .
[0111] The bioactivity test of the meniscus implant was carried out. Synovial mesenchymal stem cells were implanted on the surface of the meniscus implant and cultured for 14 days. The culture medium was replaced every day. The CCK-8 test method was used to test the bioactivity value (OD / 450nm) of the stem cells on the 14th day, which was 2.1.
[0112] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 1.5MPa to 1.7MPa.
[0113] Example 2
[0114] (1) Preparation of composite fibers for meniscus implants:
[0115] Materials: Same as Example 1.
[0116] Yarn morphology: Same as Example 1.
[0117] Fiber mat morphology: The yarns are laid in a staggered manner at 0° / 90°, and then the polyvinyl alcohol and deionized water are mixed in a certain proportion, and stirred at a constant speed for 1 hour to uniformly disperse the adhesive to form a solution. The mixed solution is sprayed onto the fiber surface by a surface spraying process, and placed in a 60°C oven for 1 hour to form a stable fiber mat.
[0118] (2) Preparation of meniscus implant matrix:
[0119] Same as Example 1.
[0120] (3) Preparation of meniscus implants:
[0121] Same as Example 1.
[0122] (4) Performance characterization of meniscus implants:
[0123] The calcium ion release rate was 1×10 -9 kg m -2 s -1 .
[0124] The bioactivity test of the meniscus implant was performed. During the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 2.1.
[0125] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 1.3MPa to 1.4MPa.
[0126] Example 3
[0127] (1) Preparation of composite fibers for meniscus implants:
[0128] Materials: Same as Example 1.
[0129] Yarn morphology: Same as Example 1.
[0130] Fiber felt morphology: same as in Example 2.
[0131] (2) Preparation of meniscus implant matrix:
[0132] Same as Example 1.
[0133] (3) Preparation of meniscus implants:
[0134] Component content: Same as Example 1.
[0135] Preparation of customized molds: First, perform MRI on the patient's knee joint to obtain a 2D MRI image of the knee joint, obtain a 3D model of the damaged meniscus through image processing, mirror the 3D model to obtain a 3D model of the meniscus suitable for the injured side, then make a 3D mold model by remolding, and prepare a light-transmitting customized 3D mold by cutting PMMA material through CNC machining;
[0136] Molding process: Based on a customized mold, the same freeze-thaw molding process as in Example 1 was adopted.
[0137] (4) Performance characterization of meniscus implants:
[0138] The calcium ion release rate was 1×10 -9 kg m -2 s -1 .
[0139] The bioactivity test of the meniscus implants was performed, and during the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 2.1.
[0140] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 1.8MPa to 2.1MPa.
[0141] Example 4
[0142] (1) Preparation of composite fibers for meniscus implants:
[0143] Materials: Polyvinyl alcohol fiber is used as the reinforcement structure, and the mass content of doped calcium phosphate is 1.5%.
[0144] Yarn form: PVA fiber and silk fiber are twisted in S-twist form with a twist of 40 twists / m to form single yarn, and then the two are twisted and compounded in Z-twist form to form a plied yarn with a twist of 40 twists / m.
[0145] Fiber mat form: The yarn is woven in plain weave to form a fiber fabric structure, and then polyvinyl alcohol is mixed with deionized water to fully disperse it, and a homogeneous mixed solution is formed by stirring at a constant speed for 1 hour. The fiber fabric is immersed in the solution for 0.5 hours, and then taken out and placed in a 60°C oven for 1 hour to form a stable fiber mat.
[0146] (2) Preparation of meniscus implant matrix:
[0147] Materials: Polyacrylamide is used as the meniscus matrix.
[0148] Preparation of platelet-rich plasma: Same as Example 1.
[0149] Molding process: Using the photocuring resin process, the initiator (2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP)) and the monomer (polyacrylamide) are mixed in a ratio of 0.1:100 to obtain a transparent mixed hydrogel precursor solution; then the treated PRP and the hydrogel precursor solution are evenly mixed in a ratio of 1:10, and dispersed with magnetic stirring at 500RPM / min at room temperature for 2 hours to obtain a homogeneous photosensitive resin for photocuring and cross-linking.
[0150] (3) Preparation of meniscus implants:
[0151] Component content: Same as Example 1.
[0152] Customized mold preparation: same as Example 3;
[0153] Molding process: The photocuring molding process is used to stack the cut continuous composite fiber felt in a transparent mold, connect the catheter, and inject the hydrogel precursor liquid into the mold at a uniform speed to allow the precursor liquid to completely infiltrate the composite fiber felt. The hydrogel precursor liquid is cross-linked under ultraviolet light for 1 hour, and then the artificial meniscus implant is removed.
[0154] (4) Performance characterization of meniscus implants:
[0155] The ion release rate analysis showed that the calcium ion release rate was 0.3×10 -9 kg m -2 s -1 .
[0156] The bioactivity test of the meniscus implants was performed, and during the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 1.2.
[0157] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 1.6MPa to 1.8MPa.
[0158] Example 5
[0159] (1) Preparation of composite fibers for meniscus implants:
[0160] Material: Polylactic acid fiber is used as the reinforcement structure, and the mass content of doped calcium phosphate is 2%.
[0161] Yarn morphology: Same as Example 4.
[0162] Fiber felt morphology: same as in Example 4.
[0163] (2) Preparation of meniscus implant matrix:
[0164] Same as Example 4.
[0165] (3) Preparation of meniscus implants:
[0166] Same as Example 4.
[0167] (4) Performance characterization of meniscus implants:
[0168] The ion release rate analysis showed that the calcium ion release rate was 0.5×10 -9 kg m -2 s -1 .
[0169] The bioactivity test of the meniscus implants was performed, and during the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 1.5.
[0170] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 1.8MPa to 1.9MPa.
[0171] Example 6
[0172] (1) Preparation of composite fibers for meniscus implants:
[0173] Material: Polycaprolactone fiber is used as the reinforcement structure, and the mass content of doped calcium phosphate is 2.5%.
[0174] Yarn morphology: Same as Example 4.
[0175] Fiber felt morphology: same as in Example 4.
[0176] (2) Preparation of meniscus implant matrix:
[0177] Same as Example 4.
[0178] (3) Preparation of meniscus implants:
[0179] Same as Example 4.
[0180] (4) Performance characterization of meniscus implants:
[0181] The calcium ion release rate was 0.9×10 -9 kg m -2 s -1 .
[0182] The bioactivity test of the meniscus implants was performed, and during the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 1.8.
[0183] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 2.1MPa to 2.3MPa.
[0184] Example 7
[0185] (1) Preparation of composite fibers for meniscus implants:
[0186] Materials: The reinforced structure is made of degradable calcium phosphate glass fiber, in which the mass ratio of calcium is 0.05%.
[0187] Yarn form: Calcium phosphate glass fiber and silk fiber are twisted in S-twist form with a twist of 10 twists / m to form a single yarn, and then the two are twisted and compounded in Z-twist form to form a plied yarn with a twist of 10 twists / m.
[0188] Fiber mat morphology: The yarn is woven in plain weave to form a fiber fabric structure, and then polyvinyl alcohol is mixed with deionized water to fully disperse it, and a homogeneous mixed solution is formed by stirring at a constant speed for 1 hour. The fiber fabric is immersed in the solution for 0.5 hours, and then taken out and placed in a 60°C oven for 1 hour to form a stable fiber mat.
[0189] (2) Preparation of meniscus implant matrix:
[0190] Materials: Polyvinyl alcohol is used as the meniscus matrix.
[0191] Preparation of platelet-rich plasma: 50 mL of venous blood was drawn from the patient, 10% sodium citrate anticoagulant was added, and the blood was centrifuged for 10 min using gradient centrifugation (differential centrifugation). The upper plasma layer and the solution above 2 mm below the dividing line were aspirated into a new centrifuge tube, and the blood was centrifuged again for 10 min. 2 mL of PRP was taken from the lower layer, and the blood was shaken for 30 s to obtain concentrated PRP.
[0192] Molding process: Using the freeze-thaw process, the polyvinyl alcohol pellets were evenly mixed with deionized water in a mass ratio of 1:8, and magnetically stirred at 300RPM / min in a 60°C water bath for 1 hour to form a homogeneous solution. The treated PRP and hydrogel precursor solution were evenly mixed in a ratio of 1:5, and dispersed by magnetic stirring at 300RPM / min at room temperature. Then, the bubbles were removed by vacuum in a vacuum box at 50°C to form a homogeneous, bubble-free, low-viscosity hydrogel precursor solution.
[0193] (3) Preparation of meniscus implants:
[0194] Component content: The fiber-reinforced structure accounts for 15% by weight in the meniscus implant.
[0195] Molding process: Standard mold molding is adopted, based on resin transfer molding (RTM) technology, the cut fiber felts are stacked in the RTM mold, the catheter is connected, and the hydrogel precursor is injected into the mold at a uniform speed to make the precursor completely infiltrate the composite fiber felt. According to the freeze-thaw method, it is frozen and cross-linked at -30°C for 8 hours, and then thawed at 1°C for 8 hours. This cycle is repeated 6 times, and then the artificial meniscus implant is removed.
[0196] (4) Performance characterization of meniscus implants:
[0197] The calcium ion release rate was 3×10 -10 kg m -2 s -1 .
[0198] The bioactivity test of the meniscus implant was performed. During the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 1.5.
[0199] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 0.5MPa to 0.7MPa.
[0200] Example 8
[0201] (1) Preparation of composite fibers for meniscus implants:
[0202] Materials: The reinforced structure is made of degradable calcium phosphate glass fiber, in which the calcium element accounts for 3% by mass.
[0203] Yarn form: Calcium phosphate glass fiber and silk fiber are twisted in S-twist form with a twist of 60 twists / m to form a single yarn, and then the two are twisted and compounded in Z-twist form to form a plied yarn with a twist of 60 twists / m.
[0204] Fiber mat morphology: The yarn is woven in plain weave to form a fiber fabric structure, and then polyvinyl alcohol is mixed with deionized water to fully disperse it, and a homogeneous mixed solution is formed by stirring at a constant speed for 1 hour. The fiber fabric is immersed in the solution for 0.5 hours, and then taken out and placed in a 60°C oven for 1 hour to form a stable fiber mat.
[0205] (2) Preparation of meniscus implant matrix:
[0206] Materials: Polyvinyl alcohol is used as the meniscus matrix.
[0207] Preparation of platelet-rich plasma: 50 mL of venous blood was drawn from the patient, 10% sodium citrate anticoagulant was added, and the blood was centrifuged for 10 min using gradient centrifugation (differential centrifugation). The upper plasma layer and the solution above 2 mm below the dividing line were aspirated into a new centrifuge tube, and the blood was centrifuged again for 10 min. 2 mL of PRP was taken from the lower layer, and the blood was shaken for 30 s to obtain concentrated PRP.
[0208] Molding process: Using the freeze-thaw process, the polyvinyl alcohol pellets were evenly mixed with deionized water in a mass ratio of 1:10, and magnetically stirred at 300RPM / min in a 60°C water bath for 1 hour to form a homogeneous solution. The treated PRP and hydrogel precursor solution were evenly mixed in a ratio of 1:15, and dispersed by magnetic stirring at 300RPM / min at room temperature. Then, the bubbles were removed by vacuum in a vacuum box at 50°C to form a homogeneous, bubble-free, low-viscosity hydrogel precursor solution.
[0209] (3) Preparation of meniscus implants:
[0210] Component content: The fiber-reinforced structure accounts for 55% of the meniscus implant by weight.
[0211] Molding process: Standard mold molding is used, based on resin transfer molding (RTM) technology, the cut fiber felts are stacked in the RTM mold, the catheter is connected, and the hydrogel precursor is injected into the mold at a uniform speed to allow the precursor to completely infiltrate the composite fiber felt. According to the freeze-thaw method, it is frozen and cross-linked at -10°C for 6 hours, and then thawed at 8°C for 6 hours. This cycle is repeated 5 times, and then the artificial meniscus implant is removed.
[0212] (4) Performance characterization of meniscus implants:
[0213] The calcium ion release rate was 2.4×10 -9 kg m -2 s -1 .
[0214] The bioactivity test of the meniscus implant was performed. During the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 2.4.
[0215] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus increased from 2.2MPa to 2.4MPa.
[0216] Comparative Example 1
[0217] (1) Preparation of meniscus implant reinforcement fibers:
[0218] Same as Example 1.
[0219] (2) Preparation of meniscus implant matrix:
[0220] No PRP was added and the remaining steps were the same as in Example 1.
[0221] (3) Preparation of meniscus implants:
[0222] Same as Example 1.
[0223] (4) Performance characterization of meniscus implants:
[0224] The calcium ion release rate was 1×10 -9 kg m -2 s -1 .
[0225] The bioactivity test of the meniscus implants was carried out. During the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 1.1.
[0226] Before and after the biological test, through compressive strength analysis, the mechanical strength of the meniscus decreased from 1.5MPa to 1.2MPa.
[0227] Comparative Example 2
[0228] (1) Preparation of meniscus implant reinforcement fibers:
[0229] No fiber reinforcement.
[0230] (2) Preparation of meniscus implant matrix:
[0231] No PRP was added and the remaining steps were the same as in Example 1.
[0232] (3) Preparation of meniscus implants:
[0233] Same as Example 1.
[0234] (4) Performance characterization of meniscus implants:
[0235] No calcium ion release.
[0236] The bioactivity test of the meniscus implants was carried out. During the 14-day culture of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 0.6.
[0237] Before and after biological testing, through compressive strength analysis, the mechanical strength of the meniscus decreased from 0.4MPa to 0.3MPa.
[0238] Comparative Example 3
[0239] (1) Preparation of meniscus implant reinforcement fibers:
[0240] Same as Example 1, but without silk fibers.
[0241] (2) Preparation of meniscus implant matrix:
[0242] Same as Example 1.
[0243] (3) Preparation of meniscus implants:
[0244] Same as Example 1.
[0245] (4) Performance characterization of meniscus implants:
[0246] The calcium ion release rate was 1×10 -9 kg m -2 s -1 .
[0247] The bioactivity test of the meniscus implants was carried out. During the 14-day culturing of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 1.1.
[0248] Before and after the biological test, through compressive strength analysis, the mechanical strength of the meniscus decreased from 1.1MPa to 0.7MPa.
[0249] Comparative Example 4
[0250] (1) Preparation of composite fibers for meniscus implants:
[0251] Same as Example 4, but without calcium phosphate doping.
[0252] (2) Preparation of meniscus implant matrix:
[0253] Same as Example 4.
[0254] (3) Preparation of meniscus implants:
[0255] Same as Example 4.
[0256] (4) Performance characterization of meniscus implants:
[0257] No calcium ion release was observed.
[0258] The bioactivity test of the meniscus implants was carried out. During the 14-day culture of synovial mesenchymal stem cells, the cell activity optical density (OD / 450nm) of the cells on the 14th day was 0.6.
[0259] Before and after the biological test, through compressive strength analysis, the mechanical strength of the meniscus decreased from 1.6MPa to 0.5MPa.
[0260] Table 1: Formulation design and implementation effect of meniscus implants in embodiments and comparative examples
[0261]
[0262]
[0263] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A meniscus implant, characterized in that: including degradable hydrogels, composite fibers, and platelet-rich plasma; The meniscus implant uses a degradable hydrogel as a matrix and composite fibers as a skeleton; the composite fibers and platelet-rich plasma are distributed inside the degradable hydrogel; The composite fiber is mainly obtained by composite twisting of degradable fiber and silk fiber; the degradable fiber releases calcium ions after degradation.
2. The meniscus implant according to claim 1, characterized in that: The degradable hydrogel is mainly obtained by cross-linking a precursor solution; Preferably, the precursor comprises at least one of silk fibroin, agarose, alginate, collagen, gelatin, hyaluronic acid, chitosan, gellan gum, cellulose, fibrin, polyvinyl alcohol, polyethylene glycol, polyacrylamide or poly(hydroxyethyl methacrylate); Preferably, in the precursor solution, the mass ratio of the precursor to water is 1:5 to 1:10; Preferably, the mass ratio of the platelet-rich plasma to the precursor solution is 1:5 to 1:
15.
3. The meniscus implant according to claim 1, characterized in that: The mass proportion of the composite fiber is 15% to 55%; Preferably, the twist of the composite fiber is 10 to 60 twists / m; Preferably, in the composite fiber, the volume ratio of the degradable fiber to the silk fiber is 1:0.5 to 1:5; Preferably, in the meniscus implant, the composite fibers are braided into a braid.
4. The meniscus implant according to claim 1, characterized in that: The degradable fiber is a degradable inorganic fiber; Preferably, the degradable inorganic fiber comprises calcium phosphate-based glass fiber; Preferably, the mass percentage of calcium in the degradable inorganic fiber is 0.05% to 3%.
5. The meniscus implant according to claim 1, characterized in that: The degradable fiber is a degradable organic fiber; Preferably, the degradable organic fiber comprises polyvinyl alcohol fiber, polyvinyl pyrrolidone, polylactic acid or polycaprolactone; Preferably, the degradable organic fiber is doped with a soluble calcium salt; Preferably, the soluble calcium salt includes calcium chloride, and the mass proportion of the soluble calcium salt in the degradable organic fiber is 0.1% to 5%.
6. The method for preparing the meniscus implant according to any one of claims 1 to 5, characterized in that: The following steps are involved: a. preparing a precursor solution of the degradable hydrogel, and then mixing it with platelet-rich plasma to obtain a precursor mixed solution; b. Weaving the composite fibers to obtain a braided fabric, then stacking the braided fabric in a mold, adding the precursor mixed solution obtained in step a, and preparing a meniscus implant after cross-linking.
7. The preparation method according to claim 6, characterized in that: The composite fibers in the braided fabric are bonded with a binder.
8. The preparation method according to claim 6, characterized in that: The precursor is at least one of polyvinyl alcohol, hyaluronic acid, chitosan, gelatin, cellulose or agarose; The cross-linking method comprises: freezing and cross-linking the precursor mixed solution in an environment of -30 to -10°C for 6 to 12 hours, then thawing in an environment of 0 to 8°C for 6 to 12 hours, and preparing a meniscus implant after 3 to 6 cycles.
9. The preparation method according to claim 6, characterized in that: The precursor is at least one of polyacrylamide, polyhydroxyethyl methacrylate, silk fibroin, alginate, collagen, gellan gum, fibrin or polyethylene glycol; The precursor mixed solution also contains a photoinitiator and a monomer; The cross-linking method comprises: cross-linking a precursor mixed solution under ultraviolet light for 0.5 to 3 hours to prepare a meniscus implant.
10. The preparation method according to claim 9, characterized in that: The photoinitiator and the monomer are mixed in a mass ratio of 0.01:100 to 1:100; Preferably, the photoinitiator comprises at least one of phenyl-2,4,6-trimethylbenzoyl lithium phosphite, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide; Preferably, the monomer includes at least one of a polyacrylamide monomer, a polyhydroxyethyl methacrylate monomer or a polyurethane acrylate monomer.
Citation Information
Patent Citations
Artificial meniscus scaffold based on fiber braided structure and braiding method of meniscus scaffold
CN107669373A
A porous composite scaffold for promoting cartilage regeneration and its preparation method
CN107789667B
Biomimetic osteochondral complex and preparation method thereof
CN108404214A
Artificial meniscus including circumferential and non-circumferential fiber bundles
US20210137691A1
Cited By
Preparation method and application of micro air bag reinforced high-order structure anti-fatigue hydrogel
CN120329570A
Meniscus implant and preparation method therefor
WO2026118865A1